Tingkat Ketergantungan Fiskal dan Hubungannya dengan Pertumbuhan Ekonomi di Kota Jambi - Muhammad Ariansyah; Amri Amir; Erni Achmad (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
This research aims to calculate Fiscal Needs in Jambi City and analyze the level of dependence on Fiscal relations with the Economic Growth in Jambi and see how much the rate dependence of the Fiscal Jambi City to the Central Government. These results indicate that the Fiscal Needs in Jambi city has increased significantly each year, the average growth of 46.28 %. Local Government Fiscal Dependence level of Jambi City to the Central Government is very High, the average in the past 11 years (2000 s / d 2010) the proportion of PAD to the total of the local revenue obtained an average of 9.6% and the proportion of average fund balance of the total of local revenues obtained an average of 90.4%, The relationship between the level of fiscal dependence with the Economic Growth in Jambi is very low, amounting to only 0.068.Keywords: Fiscal Need, Local Revenue, Fiscal Dependence